2021
DOI: 10.1021/acs.est.0c07191
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Solar Distillation for Freshwater Production: Fate of Volatile and Semivolatile Organic Contaminants

Abstract: Interfacial solar distillation (ISD) is an approach with low cost and low energy demand useful for seawater desalination and freshwater production. However, the commercial potential of ISD for applications such as polluted seawater desalination or industrial wastewater reuse may be hindered by low rejection of volatile and semivolatile contaminants. For the first time, the results of this study showed that the transport (from bulk water (B) to distilled water (D)) of volatile and semivolatile contaminants duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…As some of the most prolific VOCs, phenolic compounds deserve the most attention in condensed freshwater due to their high contaminant distillation concentration ratio . Phenolic compounds with different substituent groups such as phenol, p -methylphenol, and p -chlorophenol were selected as the typical VOCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As some of the most prolific VOCs, phenolic compounds deserve the most attention in condensed freshwater due to their high contaminant distillation concentration ratio . Phenolic compounds with different substituent groups such as phenol, p -methylphenol, and p -chlorophenol were selected as the typical VOCs.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds with different substituent groups such as phenol, p -methylphenol, and p -chlorophenol were selected as the typical VOCs. Here, the “contaminant’s distillation concentration ratio ( R D , eq )” was used to evaluate the specific contaminant’s concentration in condensed freshwater. The low R D value indicates low contaminant concentration in condensed freshwater where C D and C B are the concentrations of the contaminants in condensed freshwater and the initial simulated seawater, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…During evaporation, some volatile contaminants will escape, condense, and be collected along with water vapor. Although a few studies proposed that the use of activated carbon with good adsorption capacity as a photothermal material could effectively reduce the content of volatile contaminants in condensates, 78,280 the issue of limited service life caused by adsorption saturation has not yet been resolved. Therefore, there is an urgent need to develop SIE systems for the treatment of water sources containing volatile contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the migration of volatile and semivolatile contaminants from bulk to distilled water during the interfacial solar evaporation process highly depends on compound volatility. 110 This research showed that phenols and similar compounds with high volatilization and condensation rates could easily move to the distillate water side. Adsorption via activated carbon and photothermal oxidation were suggested as promising strategies for ensuring water safety.…”
Section: Advanced Characteristics Of Aerogels For Effective Freshwate...mentioning
confidence: 92%